Dennis Lehane e Martin Scorsese: dois olhares sobre a construção da personagem Edward “Teddy” Daniels de Ilha do medo - Gomes, Fernando Franqueiro (2018)
This work aims to analyze the construction of the character Edward “Teddy” Daniels, from the novel Shutter Island (2003), written by the author Dennis Lehane, and how it is built in the film adaptation directed by Martin Scorsese (2010). In this study the process of film adaptation will be worked through the notion of intersemiotic translation. The elements of the narrative that contribute to the construction of the character in the written novel will be analyzed such as the violence surround his experiences, the conflicts that helps to build his persona and the influence of noir style in the character, and how these elements are translated into the language of cinema. With the theoretical support of reflection such as those from Roland Barthes, Jean Epstein, Serguei Eisenstein, Muniz Sodré and Pedro Butcher, among others, this work contextualizes the dialog stablished between literature and cinema, considering the objects of this work as products of the mass culture. A study about adaptation of literary texts for the cinema as a form of translation will also be carried out based on authors as Julio Plaza, Linda Hutcheon, Thaís Flores Nogueira Diniz and Haroldo de Campos. The fictional trajectory of the writer and the filmmaker is also presented, with emphasis on the thematic dialogues that becomes evident between Dennis Lehane and Martin Scorsese. Edward "Teddy" Daniels can be considered as the main piece that conducts the entire development of the romance and movie plot, and his analysis will be done based on studies that approach the character construction and the use of noir narrative on both literature and cinema, such as Roberta Nichele Bastos, Alain Silver and James Ursini, Vitor Manuel de Aguiar e Silva and Fernanda Massi. The intersemiotic translation will also be observed to recreate the character in the movie adaptation, through the language of cinema, under Martin Scorsese's direction.